Robinson’s Theme in the English Children and Juvenile Literature at the End of the 19th and the Beginning of the 20th Centuries - Bramane, Rita (Respectus Philologicus, 2004)
The story about Robinson Crusoe has never lost its popularity and fascination. The article discusses different versions of the plot and modifications of the story narrated by Daniel Defoe. The author’s influence on the subsequent world literature of adventures is also being analyzed. The main focus is on the spatial-time model of the island in the works of R. L. Stevenson and G. M. Barrie and on the diverse interpretations of the idea of "an island" in the works of different writers.